Profil Life Skill Berbasis Problem Solving di PKBM Sinar Lentera - Raudah Zaimah Dalimunthe; Herlina Siregar; Ahmad Fauzi; Dede Rahmat Hidayat; Arga Satrio Prabowo; Ika Rizqi Meilya (Jurnal Penelitian Bimbingan dan Konseling, 2020)
This study aims to describe the profile of problem solving based skill life skills. This research was conducted at PKBM Sinar Lentera which is located at Jl. Kp. RT RT. 04 Rw. 08 Ex. Pagerbatu Kec. Majasari Pandeglang Regency Banten with a sample of respondents who were sources of information from the PKBM chair, learning residents, and tutors. The research method used is research and development which is divided into three stages, namely: 1) qualitative description analysis. Each research subject was collected through the Social Problem Solving Inventory-Revised instrument. The indicators in the instrument are: (1) unproductive problem solving techniques and helpless attitudes towards problem solving, (2) effective & systematic problem solving techniques. The results of this study are in general it can be concluded that the skill of life skills based on problem solving in PKBM Sinar Lentera is in the medium category.